Biomimetic Janus chitin nanofiber membrane for potential guided bone regeneration application. (1st January 2021) - Prajatelistia, Ekavianty; Sanandiya, Naresh D.; Nurrochman, Andrieanto; Marseli, Fresty; Choy, Seunghwan; Hwang, Dong Soo
Graphical abstract: Biomimetic Janus guided bone regeneration membrane composed of antifouling MPC layer facing soft tissue which suppress the fibroblast attachment, and chitin nanofibers network facing alveolar ridge which support the bone formation. Highlights: Chitin-based Two-faced membrane (ChN/PMT) was successfully fabricated. The membrane shows a higher proliferation rate of osteoblast on the chitin side. The membrane shows a lower proliferation rate of fibroblast on PMT side. ALP activity suggests the ability to maintain the differentiation of osteogenic cells. The ChN/PMT membrane has the potential for guided bone regeneration. Abstract: Biopolymer-based membranes are at the forefront of the guided bone regeneration (GBR) in orthopaedics and dentistry, which prevent fast-growing soft tissue migration to the defected alveolar ridge or implants and allow the bone regeneration. In this study, we fabricated a novel Janus -two-faced, GBR membrane composed of a chitin nanofiber face for bone regeneration and a cell membrane mimetic antifouling 2-Methacryloyloxyethyl phosphorylcholine (MPC) polymeric face for suppressing the migration of the soft tissue. In vitro cell study showed a higher cell proliferation rate of osteoblast cells on the chitin nanofiber surface and a lower proliferation rate of fibroblasts cells on the antifouling MPC side. An increased of Alkaline Phosphatase (ALP) rate was observed in the chitin nanofiber face, indicating the ability to maintain proliferation and differentiation of osteogenic cells. These results suggest the biomimetic Janus chitin membrane may have the potential to develop as an advance GBR membrane.